Odpowiedzi

Najlepsza Odpowiedź!
2010-03-24T18:42:16+01:00
A) 9+x=1⅞
x=1⅞-9
x=-8⅞

b) 8a+4=36
8a=36-4
8a=32 /:8
a=4

c) 6b-3=-9
6b=-9+3
6b=-6 /:6
b=-1

d) -2,5c-8=17
-2,5c=17+8
-2,5c=25 /: (-2,5)
c=-10

e) 0,4m-2=-6
0,4m=-6+2
0,4m=-4 /:0,4
m=-10

Polecam się ;)
  • ka1
  • Początkujący
2010-03-24T18:43:58+01:00
A) 9+x=1⅞
x=1,847-9
x=-7,125
b) 8a+4=36
8a=36-4
8a=32/:8
a=4
c)6b-3=-9
6b=-9+3
6b=-6/:6
b=-1
d)-2,5c-8=17
-2,5c=17+8
-2,5c=25/:(-2,5)
c=-10
e)0,4m-2=-6
0,4m=-6+2
0,4m=-4/:0,4
m=-10




1 4 1
2010-03-24T18:46:20+01:00
9+x=1⅞
x= 1⅞-9
x=-16/8
x=-2

8a+4=36
8a=32 /÷8
a=4

6b-3=9
6b=12 /÷6
b=2

-2,5c-8=17
-2,5c=25 /÷(-2,5)
c= -0,1


0,4m-2=-6
0,4m=-4 /÷0,4
m=-0,1